Recovery as an explanatory mechanism in the relation between acute stress reactions and chronic health impairment - Geurts, Sabine AE; Sonnentag, Sabine (Scandinavian Journal of Work, Environment & Health, 2006)
This contribution aims at shedding light on the mechanisms that may underlie the relationship between acute reactions to stressful work characteristics and employee health in the long run. Recovery, a process of psychophysiological unwinding after effort expenditure, is considered a vital link in this relationship. This link is explained on the basis of assumptions from theories on effort, recovery, and sustained activation. It is argued that recovery after work (external recovery) is particularly necessitated when recovery opportunities during worktime (internal recovery) are insufficient. It is further argued that two conditions may impede the recovery process by sustaining physiological activation, prolonged exposure to work demands (working long hours) and cognitive stress-related processes (such as rumination). These theoretical assumptions are substantiated by empirical support from previous laboratory and field research. It is concluded that the chronic situation of sustained physiological activation and incomplete recovery is an important pathway to chronic health impairment.
Keywords: acute stress reaction; allostatic load; chronic health impairment; effort; explanatory mechanism; load reaction; nonwork; psychophysiological; recovery; recuperation; sustained activation; unwinding; work